GABA-Aα5 Might Be Involved in Learning-Memory Dysfunction in the Offsprings of Chronic Ethanol-Treated Rats via GABA-Aα5 Histone H3K9 Acetylation - Zeng, Kuan; Xie, Aimin; Dong, Xiaojie; Jiang, Jia; Hao, Wei; Jiang, Min; Liu, Xuebing (Frontiers in Neuroscience, 2019)
Recently, numerous studies have been focused on the relationship between GABA-A receptors and alcohol-induced spatial learning and memory deficits. GABA-Aα5, a subunit of GABA-A receptors, is considered to play an important role in alcohol-induced cognitive impairment, however, the mechanism remains obscure. In this study, we found that the expression of GABA-Aα5 increased in rats treated with chronic ethanol via histone H3K9 acetylation. Furthermore, this epigenetic modification could be inherited by the next generations, which eventually exhibit similar spatial learning and memory deficits in the offsprings. In summary, our results suggested that GABA-Aα5 might be involved in chronic ethanol treatment-induced learning-memory dysfunction and for the first time proved that learning-memory dysfunction could be inherited by the offsprings via histone H3K9 acetylation. Hopefully, in the near future, GABA-Aα5 inhibitors would be an effective way to treat alcohol-induced cognition impairment.